Thomas Keneally's career and the literary machine - Sharrad, Paul (Anthem studies in Australian literature and culture., 2019)
Thomas Keneally: world success story or Australian writer who never fulfilled early potential? 'Thomas Keneally's Career and the Literary Machine' explains the disparate opinions, charting his writing's production and reception as shaping a literary career. It tracks tensions between literary and commercial values, national and international expectations, celebrity status and literary reputation.